2015
DOI: 10.1118/1.4925003
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐640: Proton Modulated Arc Therapy Using Scanned Pencil Beams

Abstract: Purpose: Rotational proton radiotherapy would be an interesting treatment modality if it proves to produce dose distributions that conform to the target as well or better than currently available treatment modalities, while reducing the dose to the surrounding organs at risk. A treatment planning study is presented, showing how this objective can be achieved using a single or small number of scanned mono‐energetic pencil beams delivered while the proton gantry rotates at the same time that they may deliver fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Besides, a recent study in prostate cancer has found that it is not possible to simultaneously meet the tumor and rectal constrains for both physical and variable RBE‐weighted dose, the latter being estimated based on in vitro cell survival data. In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions or proposing new beam orientations or treatment modalities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a recent study in prostate cancer has found that it is not possible to simultaneously meet the tumor and rectal constrains for both physical and variable RBE‐weighted dose, the latter being estimated based on in vitro cell survival data. In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions or proposing new beam orientations or treatment modalities …”
Section: Introductionmentioning
confidence: 99%
“…In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions [35][36][37][38][39] or proposing new beam orientations or treatment modalities. [40][41][42] Our proposed solution is the use of a mixed RBE model (MultiRBE) for plan optimization, where a uniform RBE is used in the target contours to ensure an adequate tumor coverage in terms of physical dose, but a variable RBE is used elsewhere. This solution incorporates the benefits of both approaches: it produces a quantifiable, numeric RBE quantity that can be used for weighting of physical dose, but it also ensures appropriate coverage of the target with a flat physical dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…A group at the University of Pennsylvania (Philadelphia, PA) did publish some work on the feasibility of delivering proton arcs using passively scattered (PS) beams ( 64 , 65 ) but with the global market moving inevitably towards pencil beam scanning (PBS) solutions, no new developments involving PS beams were realistic at the time. The same group also explored the feasibility of arc techniques with PBS ( 66 ), showing that, with an adequate range selection system, single- and dual-energy proton arcs (named Proton Modulated Arc Therapy, or PMAT) could achieve similar dose coverage and organ-at-risk sparing capabilities as full-coverage 2-field and 4-field intensity-modulated proton therapy (IMPT) plans ( 67 ). The same study also showed limited improvement by using fully modulated arcs, warning that existing planning systems might not be able to produce optimal proton arc therapy plans by simply combining an arbitrarily large number of field angles in an IMPT plan, and that specific treatment-planning algorithms for proton arc therapy, either developed in-house ( 68 , 69 ) or as an addition to existing systems ( 70 ) are probably required.…”
Section: Mechanics: the Advantages And Limits Of Arcs And Gantry-lessmentioning
confidence: 99%
“…The understanding of the mechanisms behind the FLASH effect when delivered with PBS beams is extremely limited, in part due to the difficulty of characterizing the beam dynamics at the FLASH timescale; therefore, most current studies only do this with simulation (Jolly et al 2020). Similarly, further clinical studies are needed to demonstrate the benefits of proton arc to IMPT plans, where current beam stability and pause uncertainties need to be resolved (Carabe-Fernandez et al 2015). Developing QA devices and workflows will be essential for the translation of either technique to routine clinical use (Li 2019).…”
Section: Introductionmentioning
confidence: 99%